Amico galaxy clusters in KiDS-DR3: sample properties and selection function - Maturi, Matteo (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present the first catalogue of galaxy cluster candidates derived from the third data release of the Kilo-Degree Survey. The sample of clusters has
Gesehen am 25.06.2020